PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PERDAGANGAN SATWA LIAR YANG DILINDUNGI MENURUT UNDANG-UNDANG NOMOR 5 TAHUN 1990 TENTANG KONSERVASI SUMBER DAYA ALAM HAYATI DAN EKOSISTEMNYA (Studi Kasus Terhadap Perdagangan Burung Paruh Enggang Di Provinsi Kalimanta - RIKY ILHAMSYAH DININGRAT,SH A.2121028, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACTThis thesis discusses the enforcement of the crime of trafficking in wildlife According to Law No. 5 of 1990 about Conservation of Biological Resources and their Ecosystems (Case Study Part Hornbill Bird Against Trafficking In West Kalimantan). The method used in this research is normative juridical approach. From the results of this thesis can be concluded that law enforcement is carried out by BKSDA West Kalimantan against law violations KSDAHE not run optimally. This is because the results of the field shows that there are still many traders who sell animals that belong to the category of animals are protected by laws – laws. West Kalimantan Province not providing socialization and education to traders on the characteristics and types of animals, including protected by laws - laws, a lack of intensity BKSDA West Kalimantan Province in examinations in the means bird markets in West Kalimantan. Constraints faced by BKSDA West Kalimantan Province in tackling violations of the law is an obstacle KSDAHE internal and external constraints. Internal constraints include the limited number and competence of labor better, minimn yes infrastructure and limited funding.While the external constraints include a lack of knowledge of the traders regarding the types and characteristics of animals protected by law, the lack of public awareness for not keeping animals that are protected because it could be considered as a means of raising the prestige, terindikasikan found leakage of information a raid by a person who is not to be responsible. Efforts BKSDA West Kalimantan Province in overcoming the obstacles encountered in tackling pelanggararan Act KSDAHE in Kalbar is the effort to overcome the internal constraints in addressing the problem of limited manpower, infrastructure and funds, BKSDA Kalbar doing filing work force, means infrastructures and funds to the forestry ministry. Meanwhile, to overcome the constraints of the limited workforce has better competence is by way of the workforce training.Efforts to overcome external obstacles to overcome external constraints, BKSDA Kalbar gave counseling to the traders there are birds in the area West Kalimantan and community outreach animal lovers to cooperate with BKSDA then do a cross-sector cooperation. Recommendations For BKSDA West Kalimantan to reinforce the implementation of the sanctions for the perpetrators of violations of the laws KSDAHE so as to improve public awareness and traders will be the importance of conserving birds of the species that exist Kalbar. BKSDA in enforcing the law in a preventive, should further increase the intensity of supervision, which is expected to oversight conducted by one (1) month of two (2) times, in order to cope with violations of the laws KSDAHE. For lovers of protected wildlife and traders to be more concerned over the sustainability of the species that exist in the provision ordinance, and not memperniagakan types of animals protected by law KSDAHE.Keywords: Law Enforcement, Crime, Trafficking,